2018
DOI: 10.1088/1755-1315/108/2/022061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonic Melt Treatment on Microstructure and Mechanical Properties of 35CrMo Steel Casting

Abstract: Abstract. Effects of different power ultrasonic on microstructure and mechanical properties of 35CrMo steel casting were investigated using optical microscopy (OM), scanning electron microscopy (SEM) and hardness testing. A self-developed experiment apparatus was used for the propagation of ultrasonic vibration into the 35CrMo steel melt to carry out ultrasonic treatment. The experimental results showed that compared to the traditional casting, ultrasonic treatment can obviously change the solidification micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In recent years, ultrasonic waves had been widely used in the field of casting because of their cavitation and acoustic flow effect, which refined the solidified structure and avoided pores and inclusions [ 5 , 6 , 7 ]. Shi et al [ 8 , 9 ] showed that the introduction of ultrasonic wave in the casting process of 35CrMo steel makes the microstructure change from coarse dendrites to fine dendrites or equi-axed grains and more pronounced grain refinement observed with increasing ultrasonic power. Liu et al [ 10 ] introduced ultrasonic waves into the casting process of AZ91 magnesium alloy and found that fine and uniform non-dendritic structure was obtained under the action of ultrasonic cavitation and flow, and the material exhibited strong yield strength.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ultrasonic waves had been widely used in the field of casting because of their cavitation and acoustic flow effect, which refined the solidified structure and avoided pores and inclusions [ 5 , 6 , 7 ]. Shi et al [ 8 , 9 ] showed that the introduction of ultrasonic wave in the casting process of 35CrMo steel makes the microstructure change from coarse dendrites to fine dendrites or equi-axed grains and more pronounced grain refinement observed with increasing ultrasonic power. Liu et al [ 10 ] introduced ultrasonic waves into the casting process of AZ91 magnesium alloy and found that fine and uniform non-dendritic structure was obtained under the action of ultrasonic cavitation and flow, and the material exhibited strong yield strength.…”
Section: Introductionmentioning
confidence: 99%